PURITY OF HEART AND SEXUALITY IN CONSECRATED VIRGINITY AND MARRIAGE: A Study on the Teaching of John Paul II in His Theology of the Body - Jose, Aruna (Asian Horizons, 2013)
Human beings, whether as consecrated virgins or marital spouses, are in a continuous search of a solution in the struggle to keep one’s heart pure (honest, generous and innocent). Bl. Pope John Paul II presented a profound and renewed reflection on the meaning of human sexuality and the virtue of purity of heart based on a personalistic perspective: a person is a blessing towards which the only proper and adequate attitude is unselfish love. Understood this way, a person does not admit of use and cannot be treated as an object of use, and, as such, the means to an end. The call to virtue of purity of heart in reference to human sexuality is an indispensable fact of living faithfully to the commitment each Christian has made in his or her vocational choice. Vocation demands self-giving and it is centralto both consecrated virginity and marriage, as the full gift of oneself to God in a personalistic way. This dissertation highlights the virtue of purity of heart as an interior truth experienced in the heart and involving a positive commitment to sexual integrity that relies on the love and reverence of God, of others and oneself. The virtue of purity of heart in reference to sexuality is a new consciousness in Christ, and a new attitude towards oneself and others.